Control of the Schottky Barrier and Contact Resistance at Metal–WSe2 Interfaces by Polymeric Doping. (11th September 2020) - Ngo, Tien Dat; Lee, Myeongjin; Yang, Zheng; Ali, Fida; Moon, Inyong; Yoo, Won Jong
Abstract: Tungsten diselenide (WSe2 ) is attracting attention because of its superior electronic and optoelectronic properties. In recent years, the number of research works related to the WSe2 ‐based field‐effect transistors (FETs) has increased dramatically. Nonetheless, the performance of 2D WSe2 is influenced sensitively by metal–semiconductor (MS) interface states, where Fermi‐level pinning is substantial. This research explores Fermi‐level depinning by doping with an n‐type polymer. In this work, spin‐coated polyvinyl alcohol (PVA) is used as an n‐type dopant for achieving low‐contact‐resistance WSe2 FETs in cases of both high‐work‐function (Pd) and low‐work‐function (In) metals. Interestingly, the increase in the Schottky barrier height resulting from the application of PVA gives rise to Fowler–Nordheim tunneling for a doped Pd‐WSe2 contact. By contrast, only direct tunneling is observed for an In‐WSe2 contact irrespective of whether the dopant is used. The barrier‐height modification after doping reveals that the improvement of the contact resistance is correlated to the enhancement of tunneling current after doping, which is consistent with the measurement results. This work suggests a practical direction for contact engineering of future WSe2 ‐based electronic devices and expands the current understanding of charge transport at the MS contact when a polymeric n‐type dopant is applied. Abstract : Fermi level depinning is observed with a WSe2 device after n‐type dopant is applied. The modulation of Schottky barrier height of the device with In and Pd contact after doping confirms the Fermi level depinning effect.